Re-analyses of “Algal” Genes Suggest a Complex Evolutionary History of Oomycetes - Wang, Qia; Sun, Hang; Huang, Jinling (Frontiers in Plant Science, 2017)
The spread of photosynthesis is one of the most important but constantly debated topics in eukaryotic evolution. Various hypotheses have been proposed to explain the plastid distribution in extant eukaryotes. Notably, the chromalveolate hypothesis suggested that multiple eukaryotic lineages were derived from a photosynthetic ancestor that had a red algal endosymbiont. As such, genes of plastid/algal origin in aplastidic chromalveolates, such as oomycetes, were considered to be important supporting evidence. Although the chromalveolate hypothesis has been seriously challenged, some of its supporting evidence has not been carefully investigated. In this study, we re-evaluate the “algal” genes from oomycetes with a larger sampling and careful phylogenetic analyses. Our data provide no conclusive support for a common photosynthetic ancestry of stramenopiles, but show that the initial estimate of “algal” genes in oomycetes was drastically inflated due to limited genome data available then for certain eukaryotic lineages. These findings also suggest that the evolutionary histories of these “algal” genes might be attributed to complex scenarios such as differential gene loss, serial endosymbioses or horizontal gene transfer.